Characterization and mechanical properties of exfoliated graphite nanoplatelets reinforced polyethylene terephthalate/polypropylene composites. Issue 15 (11th March 2014) - Inuwa, I. M.; Hassan, Azman; Samsudin, S. A.; Haafiz, M. K. Mohamad; Jawaid, M.; Majeed, K.; Razak, N. C. Abdul
ABSTRACT Recently, graphene and its derivatives have been used to develop polymer composites with improved or multifunctional properties. Exfoliated graphite nanoplatelets (GNP) reinforced composite materials based on blend of polyethylene terephthalate (PET), and polypropylene (PP) compatibilized with styrene–ethylene–butylene–styrene‐g‐maleic anhydride is prepared by melt extrusion followed by injection molding. Characterization of the composites' microstructure and morphology was conducted using field emission scanning electron microscopy, transmission electron microscopy (TEM), X‐ray diffraction analysis (XRD), and Fourier transform infrared spectroscopy (FTIR). Tensile and impact strengths of test specimens were evaluated and the results showed maximum values at 3phr GNP in both the cases. Morphological studies showed that the GNPs were uniformly dispersed within the matrix. Results from XRD analysis showed uniformly dispersed GNPs, which may not have been substantially exfoliated. FTIR spectroscopy did not show any significant change in the peak positions to suggest definitive chemical interaction between GNP and the matrix. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40582.